Causes of unrest at silicic calderas in the East African Rift: New constraints from InSAR and soil‐gas chemistry at Aluto volcano, Ethiopia. (6th August 2016) - Hutchison, William; Biggs, Juliet; Mather, Tamsin A.; Pyle, David M.; Lewi, Elias; Yirgu, Gezahegn; Caliro, Stefano; Chiodini, Giovanni; Clor, Laura E.; Fischer, Tobias P.
Abstract: Restless silicic calderas present major geological hazards, and yet many also host significant untapped geothermal resources. In East Africa, this poses a major challenge, although the calderas are largely unmonitored their geothermal resources could provide substantial economic benefits to the region. Understanding what causes unrest at these volcanoes is vital for weighing up the opportunities against the potential risks. Here we bring together new field and remote sensing observations to evaluate causes of ground deformation at Aluto, a restless silicic volcano located in the Main Ethiopian Rift (MER). Interferometric Synthetic Aperture Radar (InSAR) data reveal the temporal and spatial characteristics of a ground deformation episode that took place between 2008 and 2010. Deformation time series reveal pulses of accelerating uplift that transition to gradual long‐term subsidence, and analytical models support inflation source depths of ∼5 km. Gases escaping along the major fault zone of Aluto show high CO2 flux, and a clear magmatic carbon signature (CO2 ‐δ 13 C of −4.2‰ to −4.5‰). This provides compelling evidence that the magmatic and hydrothermal reservoirs of the complex are physically connected. We suggest that a coupled magmatic‐hydrothermal system can explain the uplift‐subsidence signals. We hypothesize that magmatic fluid injection and/or intrusion in the cap of the magmatic reservoir drives edifice‐wide inflation while subsequent deflation is related to magmatic degassing and depressurization of the hydrothermal system. These new constraints on the plumbing of Aluto yield important insights into the behavior of rift volcanic systems and will be crucial for interpreting future patterns of unrest. Key Points: New satellite radar interferometry identifies accelerating uplift pulses at Aluto volcano, Ethiopia Deformation source models suggest inflation events are linked to magmatic or fluid intrusion at 5 km CO2 ‐δ 13 C reveals connected magmatic‐hydrothermal system that could account for subsequent deflation